Role of glucose in production and repression of polygalacturonase and pectate lyase from phytopathogenic fungus Fusarium moniliforme NCIM 1276 - Niture, Suryakant K.; Kumar, Ameeta R.; Pant, Aditi (World Journal of Microbiology & Biotechnology, 2006)
A mangrove fungal isolate Fusarium moniliforme NCIM 1276 was found to produce the maximum extracellular endopolygalacturonase and pectate lyase activities in liquid medium containing 1% citrus pectin and 0.2% glucose at pH 5 and pH 8, respectively. The enzyme secretion started after 10 h, when the spores were completely germinated, and maximum production occurred after 72 h in the extracellular medium. The production of polygalacturonase was enhanced by 0.2% glucose and completely repressed by 1% glucose. Pectate lyase secretion was also induced by a similar concentration of glucose in the extracellular medium and significantly decreased at 1% glucose. Quantification of extracellular and intracellular polygalacturonase and pectate lyase protein concentrations by ELISA and immunocytolocalization data suggested that glucose may control the expression of both enzymes at a transcriptional level.
Keywords: catabolic repression; Fusarium moniliforme; inducible enzyme; pectate lyase; polygalacturonase

Comparative biochemical and structural characterizations of fungal polygalacturonases - Niture, Suryakant K. (Biologia, 2008)
Endo- and exo-polygalacturonases produced by various fungi are involved in the degradation of pectic substances. They have found a wide range of applications in the food and textile industries. Several phyto-pathogenic fungi secrete polygalacturonases and they act as virulence factors during plant pathogenesis. The comparison of biochemical properties of different fungal polygalacturonases, their mechanism of actions, structural aspects and interactions with inhibitors/proteins could be used as a possible strategy for the fungal-crop disease management. This review focuses on fungal polygalacturonases, including their regulation, comparative biochemical and structural characterizations and their interactions with inhibitors.
Keywords: pectate lyase; plant pathogenesis; polygalacturonase; polygalacturonase-inhibiting proteins

Inactivation of polygalacturonase and pectate lyase produced by pH tolerant fungus Fusarium moniliforme NCIM 1276 in a liquid medium and in the host tissue - Niture, Suryakant K.; Kumar, Ameeta R.; Parab, Pradeep B.; Pant, Aditi (Microbiological Research, 2008)
Fusarium moniliforme NCIM 1276 produced pH dependent an extracellular potygalacturonase (PG) and pectate lyase (PL) at pH 5 and pH 8, respectively. In the extracellular medium about 20.3% PG and 54% of PL protein concentrations were present in the active state at pH 5 and pH 8, respectively, whereas in intracelluarly, more than 86% of both protein contents remained in the active state at all pH tested. We found two possible reasons, end-product inhibition and effect of environmental. pH on conformation of the proteins after their release into the medium. Additionally, in infected tomato and cauliflower plants, the fungus secreted similar proteins which were located near to the epidermal and vascular regions of the hypocotyts. In infected tissues, between 26.9% and to 41.5% of PG and only 0.84% - 13.4% of PL protein concentrations were present in active state. Thus, the medium/cell sap pH and concentrations of substrate/end products seem to play an important role in fungal invasion during plant pathogenesis are discussed with current literature. (c) 2006 Elsevier GmbH. All rights reserved.
Keywords: Fusarium moniliforme; pathogenesis; pectate lyase; polygatacturonase